A polyimide film for capacitors and its production process

By combining the end anhydride-based polyamic acid solution, end isocyanate-based polybutadiene and nano-alumina hollow spheres, and adopting bidirectional stretching and imidation treatment processes, the problem of poor mechanical properties of the polyimide film at micron-level thickness is solved, and the effect of improving its tensile strength and processing performance is achieved.

CN118955969BActive Publication Date: 2025-03-11TONGLING HANGYUN ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411032373.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-03-11
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

The polyimide film has poor mechanical properties at micron-scale thickness, and its brittleness makes it prone to damage or deformation during stretching, limiting its application in automotive capacitors.

Method used

By combining the end anhydride-based polyamic acid solution, end isocyanate-based polybutadiene and nano-alumina hollow spheres, bidirectional stretching and imidation treatment processes are adopted to improve the tensile strength and processing performance of the polyimide film.

Benefits of technology

The tensile strength and elongation of the polyimide film are improved, its mechanical properties at micron-scale thicknesses are improved, and its application potential in automotive capacitors is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004970249470000031
    Figure BDA0004970249470000031
Patent Text Reader

Abstract

The invention discloses a polyimide film for capacitors and a production process thereof, belonging to the technical field of polyimide films. An anhydride-terminated polyamic acid solution, an isocyanate-terminated polybutadiene and a nano-alumina hollow sphere are prepared into a copolymer slurry, and a film is cast, biaxially stretched, and imidized to obtain a polyimide film for capacitors. The introduction of the isocyanate-terminated polybutadiene further increases the rotation ability of the polymer chain, improves the elongation at break of the polyimide film, and improves the processing performance of the micron-grade polyimide film. The nano-alumina hollow sphere has a low thermal expansion coefficient and good stability, and can balance the influence of the isocyanate-terminated polybutadiene on the thermal stability of the polyimide film. The addition of the nano-alumina hollow sphere helps to further reduce the dielectric loss of the polyimide film, which helps to use it in automotive capacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polyimide films, and in particular relates to a polyimide film for capacitors and a production process thereof. Background Art

[0002] Capacitor is an important electronic component. It consists of two conductors separated by an electrolyte. These two conductors are generally called and are widely used in various circuits and electronic equipment. Among them, locomotive capacitors are indispensable electrical equipment in urban rail transit.

[0003] The working principle of locomotive capacitors is the same as that of general capacitors, both of which are based on the accumulation and release of charges in an electric field. When voltage is applied between the two poles of the capacitor, charges accumulate on the plates, forming an electric field and storing electrical energy. When needed, the capacitor can quickly release the stored electrical energy to meet the power needs of the locomotive. With the development of high-speed railways and urban light rail, higher requirements are also placed on the performance of locomotive capacitors. Metallized polypropylene film capacitors are a common type of locomotive capacitor, with good self-healing properties, low losses, and high ripple current application characteristics. Polyimide is a polymer material with excellent performance. Polyimide film can be used at high temperatures of 250°C and can work at 400°C for several hours. This feature gives it a significant advantage in applications in high-temperature environments such as locomotive capacitors. In addition, compared with polypropylene film, polyimide film has good stability, a higher dielectric constant and better electrical insulation properties.

[0004] However, polyimide films have poor mechanical properties at micron-level thicknesses, and their brittleness makes them prone to breakage or deformation during stretching. In particular, polyimide films with a thickness below 15 μm are more difficult to process, limiting their application in automotive capacitors. Summary of the Invention

[0005] One of the purposes of the present invention is to provide a polyimide film for capacitors, which is used as a base film for metallized films of automotive capacitors; the second purpose is to provide a production process for the polyimide film for capacitors.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A production process of a polyimide film for capacitors comprises the following steps:

[0008] Add anhydride-terminated polyamic acid solution, isocyanate-terminated polybutadiene and nano-alumina hollow spheres into a reactor, stir at 20-25°C for 3-3.5 hours, add 4,4'-diaminodiphenyl ether into the reactor and continue stirring for 3-3.5 hours, add N,N-dimethylformamide to adjust the solid content to 20% to obtain a copolymer slurry, vacuum degassing, cast film on a steel belt at 200°C with a casting speed of 5-6m / min, vacuum remove the solvent at 80°C to obtain a cast film, complete biaxial stretching and imidization treatment to obtain a polyimide film for capacitors, roll it up and trim it, and complete the production process of the polyimide film for capacitors.

[0009] Furthermore, the specific methods of biaxial stretching and imidization treatment are as follows:

[0010] At a stretching temperature of 180-200°C, the cast film was longitudinally stretched for 10-15 minutes at a stretching ratio of 1:1.05, then transversely stretched for 15-20 minutes at a stretching ratio of 1:1.15, heated to 250°C and kept for 30 minutes, then heated to 280°C and kept for 30 minutes, and cooled naturally.

[0011] Furthermore, the usage ratio of the anhydride-terminated polyamic acid solution and the isocyanate-terminated polybutadiene nano-alumina hollow spheres is 30 mL: 0.25-0.35 g: 0.1-0.12 g: 0.02 g.

[0012] Furthermore, the anhydride-terminated polyamic acid solution is prepared by the following steps:

[0013] Step 1: adding trimellitic anhydride chloride and tetrahydrofuran to a reactor at 20-25° C. under nitrogen protection, stirring and mixing, adding anhydrous pyridine to the reactor, stirring at 150-200 r / min for 1 hour, adding a tetrahydrofuran solution of 11.5% by mass of 1,5-dihydroxynaphthalene to the reactor, continuing to stir for 12-14 hours, filtering, concentrating, mixing the concentrated filtrate with 0.5 times the mass of acetic anhydride, reflux at 100° C. for 10-12 hours, naturally cooling, filtering, washing the filter cake with anhydrous toluene 2-3 times, and vacuum drying to obtain an ester-bonded dianhydride monomer;

[0014] The reaction process is as follows:

[0015]

[0016] Furthermore, the mass ratio of trimellitic anhydride chloride, tetrahydrofuran, anhydrous pyridine and 1,5-dihydroxynaphthalene tetrahydrofuran solution is 10:84.5:3.8 g:33.

[0017] Step 2: Under nitrogen protection, add 4,4'-diaminodiphenyl ether and N,N-dimethylformamide to the reactor, stir at 0-4 ° C and 500-600 r / min until 4,4'-diaminodiphenyl ether is completely dissolved, and add ester bond dianhydride monomer to the reactor twice on average, with the second addition of ester bond dianhydride monomer and the first addition of ester bond dianhydride monomer separated by 30-40 minutes, and then stir and react for 10-12 hours to obtain an anhydride-terminated polyamic acid solution.

[0018] Furthermore, the usage ratio of 4,4'-diaminodiphenyl ether, N,N-dimethylformamide and ester-bonded dianhydride monomer is 1 g:30 mL:4.43 g.

[0019] Furthermore, the isocyanate-terminated polybutadiene is prepared by the following steps:

[0020] Add diphenylmethane diisocyanate and N,N-dimethylformamide into a reactor, stir at 150-300 r / min for 15-20 min, then add hydroxyl-terminated polybutadiene into the reactor, stir and react at 60-70° C. for 6-7 h to obtain isocyanate-terminated polybutadiene.

[0021] Furthermore, the mass ratio of diphenylmethane diisocyanate, N,N-dimethylformamide and hydroxyl-terminated polybutadiene is 27-27.5:100-120:100.

[0022] Furthermore, the nano-alumina hollow spheres are prepared by the following steps:

[0023] The invention adopts a soft template method, wherein ammonia water with a molar concentration of 2 mol / L, an ethanol aqueous solution with a mass fraction of 33% and hexadecyltrimethylammonium bromide are added to a reactor and stirred and mixed, and the hexadecyltrimethylammonium bromide is used as a soft template. Then, an aluminum chloride aqueous solution with a mass fraction of 24% is added to the reactor as an aluminum source. The reaction is stirred at 800-1000 r / min for 60-80 minutes. The reaction liquid is centrifuged and filtered. The filter cake is washed with deionized water for 2-3 times and heat-treated at 500°C for 5-6 hours to obtain nano-alumina hollow spheres.

[0024] Furthermore, the usage ratio of ammonia water, ethanol aqueous solution, hexadecyltrimethylammonium bromide and aluminum chloride aqueous solution is 7-8 mL:120 mL:0.5-0.8 g:120 mL.

[0025] Beneficial effects of the present invention:

[0026] The raw materials for the polyimide film for capacitors of the present invention include an anhydride-terminated polyamic acid solution, isocyanate-terminated polybutadiene, and hollow nano-alumina spheres. During the preparation of the anhydride-terminated polyamic acid solution, an ester-bonded dianhydride monomer is used to introduce an asymmetric, rigid, coplanar structure into the polymer material. This bulky, rigid structure increases the rigidity of the main chain and improves the tensile strength of the polyimide film. It also disrupts the symmetry of the molecular chains, reducing chain stacking and thereby increasing interchain free volume, improving the solubility of the polymer material and facilitating film casting.

[0027] The introduction of isocyanate-terminated polybutadiene further increases the rotational ability of the polymer chain, improving the elongation at break of the polyimide film and enhancing the processing properties of the micron-sized polyimide film. The low thermal expansion coefficient and excellent stability of the hollow nanoalumina spheres can offset the impact of the isocyanate-terminated polybutadiene on the thermal stability of the polyimide film. Furthermore, the addition of the hollow nanoalumina spheres helps further reduce the dielectric loss of the polyimide film, facilitating its application in automotive capacitors. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0029] Example 1: This example provides a polyimide film for capacitors, which is produced by the following production process:

[0030] Step 1: At 20°C and under nitrogen protection, add 10kg of trimellitic anhydride chloride and 84.5kg of tetrahydrofuran to the reactor, stir and mix, then add 3.8kg of anhydrous pyridine to the reactor, stir at 150r / min for 1h, then add 33kg of 11.5% 1,5-dihydroxynaphthalene tetrahydrofuran solution to the reactor, continue stirring for 12h, filter, concentrate, mix the concentrated filtrate with 0.5 times its mass of acetic anhydride, reflux at 100°C for 10h, cool naturally, filter, wash the filter cake twice with anhydrous toluene, and vacuum dry to obtain an ester bond dianhydride monomer.

[0031] Step 2: Under nitrogen protection, add 10 kg of 4,4'-diaminodiphenyl ether and 300 L of N,N-dimethylformamide to the reactor, stir at 0 ° C and 500 r / min until the 4,4'-diaminodiphenyl ether is completely dissolved, and add 44.3 kg of ester-bonded dianhydride monomer to the reactor in two equal portions. The second addition of the ester-bonded dianhydride monomer is 30 minutes apart from the first addition of the ester-bonded dianhydride monomer, and then stir and react for 10 hours to obtain an anhydride-terminated polyamic acid solution.

[0032] Step 3: Add 27 kg of diphenylmethane diisocyanate and 100 kg of N,N-dimethylformamide into the reactor, stir at 150 r / min for 15 minutes, then add 100 kg of hydroxyl-terminated polybutadiene into the reactor, stir and react at 60° C. for 6 hours to obtain isocyanate-terminated polybutadiene.

[0033] Step 4: Using the soft template method, 7L of ammonia water with a molar concentration of 2mol / L, 120L of ethanol aqueous solution with a mass fraction of 33% and 0.5kg of cetyltrimethylammonium bromide were added to a reactor and stirred and mixed, with cetyltrimethylammonium bromide as a soft template. Then, 120kg of aluminum chloride aqueous solution with a mass fraction of 24% was added to the reactor as an aluminum source. The reaction was stirred at 800r / min for 60min. The reaction solution was centrifuged and filtered. The filter cake was washed twice with deionized water and heat-treated at 500°C for 5h to obtain nano-alumina hollow spheres.

[0034] Step 5: Add 300L of anhydride-terminated polyamic acid solution, 2.5kg of isocyanate-terminated polybutadiene and 1kg of nano-alumina hollow spheres into the reactor, stir at 20°C for 3h, and add 0.2kg of 4,4'-diaminodiphenyl ether, anhydride-terminated polyamic acid and isocyanate-terminated polybutadiene are connected through 4,4'-diaminodiphenyl ether, stirred for 3 hours, N,N-dimethylformamide is added to adjust the solid content to 20% to obtain a copolymer slurry, vacuum degassing, cast on a steel belt at 200°C, the casting speed is 5m / min, and the solvent is vacuum removed at 80°C to obtain a cast film. At a stretching temperature of 180°C, the cast film is longitudinally stretched for 10 minutes at a stretching ratio of 1:1.05, and then transversely stretched for 15 minutes at a stretching ratio of 1:1.15. The temperature is raised to 250°C and maintained for 30 minutes, and then raised to 280°C and maintained for 30 minutes. Natural cooling is completed, and after completing the imidization treatment, a polyimide film for capacitors is obtained, which is rolled up and trimmed to complete the production process of the polyimide film for capacitors.

[0035] Example 2: This example provides a polyimide film for capacitors, which is produced by the following production process:

[0036] Step 1: At 23°C and nitrogen protection, add 10kg of trimellitic anhydride chloride and 84.5kg of tetrahydrofuran to the reactor, stir and mix, add 3.8kg of anhydrous pyridine to the reactor, stir at 180r / min for 1h, then add 33kg of 11.5% 1,5-dihydroxynaphthalene tetrahydrofuran solution to the reactor, continue stirring for 13h, filter, concentrate, mix the concentrated filtrate with 0.5 times its mass of acetic anhydride, reflux at 100°C for 11h, cool naturally, filter, wash the filter cake twice with anhydrous toluene, and vacuum dry to obtain an ester bond dianhydride monomer.

[0037] Step 2: Under nitrogen protection, add 10 kg of 4,4'-diaminodiphenyl ether and 300 L of N,N-dimethylformamide to the reactor, stir at 2 ° C and 550 r / min until the 4,4'-diaminodiphenyl ether is completely dissolved, and add 44.3 kg of ester bond dianhydride monomer to the reactor in two equal portions. The second addition of the ester bond dianhydride monomer is 35 minutes apart from the first addition of the ester bond dianhydride monomer, and then stir and react for 11 hours to obtain an anhydride-terminated polyamic acid solution.

[0038] Step 3: Add 27.2 kg of diphenylmethane diisocyanate and 110 kg of N,N-dimethylformamide into the reactor, stir at 220 r / min for 18 minutes, then add 100 kg of hydroxyl-terminated polybutadiene into the reactor, stir and react at 65° C. for 6.5 hours to obtain isocyanate-terminated polybutadiene.

[0039] Step 4: Using the soft template method, 7.5L of ammonia water with a molar concentration of 2mol / L, 120L of ethanol aqueous solution with a mass fraction of 33% and 0.65kg of cetyltrimethylammonium bromide were added to a reactor and stirred and mixed, with cetyltrimethylammonium bromide as a soft template. Then, 120kg of aluminum chloride aqueous solution with a mass fraction of 24% was added to the reactor as an aluminum source. The reaction was stirred at 900r / min for 70min. The reaction solution was centrifuged and filtered. The filter cake was washed twice with deionized water and heat-treated at 500°C for 5.5h to obtain nano-alumina hollow spheres.

[0040] Step 5: Add 300L of anhydride-terminated polyamic acid solution, 3kg of isocyanate-terminated polybutadiene and 1.1kg of nano-alumina hollow spheres into the reactor, stir at 23°C for 3.2h, and add 0.2kg of 4,4'-diaminodiphenyl ether, anhydride-terminated polyamic acid and isocyanate-terminated polybutadiene are connected through 4,4'-diaminodiphenyl ether, stirred for 3.2 hours, N,N-dimethylformamide is added to adjust the solid content to 20% to obtain a copolymer slurry, vacuum degassing, and cast on a steel belt at 200°C with a casting speed of 5.5m / min. The solvent is removed in vacuum at 80°C to obtain a cast film. At a stretching temperature of 190°C, the cast film is longitudinally stretched for 12 minutes at a stretching ratio of 1:1.05, and then transversely stretched for 18 minutes at a stretching ratio of 1:1.15. The temperature is raised to 250°C and maintained for 30 minutes, then raised to 280°C and maintained for 30 minutes, naturally cooled, and after completing the imidization treatment, a polyimide film for capacitors is obtained, which is wound and trimmed to complete the production process of polyimide film for capacitors.

[0041] Example 3: This example provides a polyimide film for capacitors, which is produced by the following production process:

[0042] Step 1: At 25°C and under nitrogen protection, add 10kg of trimellitic anhydride chloride and 84.5kg of tetrahydrofuran to the reactor, stir and mix, then add 3.8kg of anhydrous pyridine to the reactor, stir at 200r / min for 1h, then add 33kg of 11.5% 1,5-dihydroxynaphthalene tetrahydrofuran solution to the reactor, continue stirring for 14h, filter, concentrate, mix the concentrated filtrate with 0.5 times the mass of acetic anhydride, reflux at 100°C for 12h, cool naturally, filter, wash the filter cake with anhydrous toluene 3 times, and vacuum dry to obtain an ester bond dianhydride monomer.

[0043] Step 2: Under nitrogen protection, add 10 kg of 4,4'-diaminodiphenyl ether and 300 L of N,N-dimethylformamide to the reactor, stir at 4 ° C and 600 r / min until the 4,4'-diaminodiphenyl ether is completely dissolved, and add 44.3 kg of ester bond dianhydride monomer to the reactor in two equal portions. The second addition of the ester bond dianhydride monomer is 40 minutes apart from the first addition of the ester bond dianhydride monomer, and then stir and react for 12 hours to obtain an anhydride-terminated polyamic acid solution.

[0044] Step 3: Add 27.5 kg of diphenylmethane diisocyanate and 120 kg of N,N-dimethylformamide into the reactor, stir at 300 r / min for 20 min, then add 100 kg of hydroxyl-terminated polybutadiene into the reactor, stir and react at 70° C. for 7 h to obtain isocyanate-terminated polybutadiene.

[0045] Step 4: Using the soft template method, 8L of ammonia water with a molar concentration of 2mol / L, 120L of ethanol aqueous solution with a mass fraction of 33% and 0.8kg of cetyltrimethylammonium bromide were added to a reactor and stirred and mixed, with cetyltrimethylammonium bromide as a soft template. Then, 120kg of aluminum chloride aqueous solution with a mass fraction of 24% was added to the reactor as an aluminum source. The reaction was stirred at 1000r / min for 80min. The reaction solution was centrifuged and filtered. The filter cake was washed with deionized water 3 times and heat-treated at 500°C for 6h to obtain nano-alumina hollow spheres.

[0046] Step 5: Add 300L of anhydride-terminated polyamic acid solution, 3.5kg of isocyanate-terminated polybutadiene and 1.2kg of nano-alumina hollow spheres into the reactor, stir at 25°C for 3.5h, and add 0.2kg of 4,4'-diaminodiphenyl ether, anhydride-terminated polyamic acid and isocyanate-terminated polybutadiene are connected through 4,4'-diaminodiphenyl ether, stirred for 3.5 hours, N,N-dimethylformamide is added to adjust the solid content to 20% to obtain a copolymer slurry, vacuum degassing, and cast on a steel belt at 200°C with a casting speed of 6m / min. The solvent is removed in vacuum at 80°C to obtain a cast film. At a stretching temperature of 200°C, the cast film is longitudinally stretched for 15 minutes at a stretching ratio of 1:1.05, and then transversely stretched for 20 minutes at a stretching ratio of 1:1.15. The temperature is raised to 250°C and maintained for 30 minutes, and then raised to 280°C and maintained for 30 minutes. Natural cooling is completed, and after completing the imidization treatment, a polyimide film for capacitors is obtained, which is rolled up and trimmed to complete the production process of the polyimide film for capacitors.

[0047] Comparative Example 1: Based on Example 3, the nano-alumina hollow spheres were not added in step 5, and the other steps remained unchanged to prepare a polyimide film.

[0048] Comparative Example 2: Based on Example 3, no isocyanate-terminated polybutadiene was added, and the remaining steps remained unchanged to prepare a polyimide film.

[0049] Comparative Example 3: The ester-bonded dianhydride monomer was replaced with commercially available pyromellitic dianhydride, and the remaining steps remained unchanged to prepare a polyimide film.

[0050] The hydroxy-terminated polybutadiene used in the examples and comparative examples is a brand of Japan Soda with a molecular weight of 1000.

[0051] The embodiments and comparative examples all use a polyimide film with a thickness of 10 μm as a unified specification. Performance tests are performed on embodiments 1 to 3 and comparative examples 1 to 3. Under the same conditions, an Al layer is vacuum evaporated on different polyimide films using a vacuum winding coating device. Dielectric tests are performed at 25°C and 1 MHz, and the dielectric constants and dielectric losses of different polyimide films are recorded. Different polyimide films are prepared into samples with a size of 0.5 cm × 0.5 cm for mechanical property testing. The starting force is 200 N, the stretching plastic is 5 mm / min, the test is repeated 10 times and the average value is taken. The tensile strength and elongation at break of different samples are recorded. The STA449F5 comprehensive thermal analyzer is used to detect the 5% thermal decomposition temperature of different polyimide film polymers in a nitrogen atmosphere, which is marked as T5.

[0052] The results are shown in Table 1:

[0053] Table 1

[0054] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Dielectric constant 3.36 3.33 3.32 3.44 3.65 3.48 Dielectric loss 0.0118 0.0115 0.0116 0.138 0.127 0.121 Tensile strength / MPa 145 148 144 140 150 133 Elongation at break / % 38 36 39 35 25 36 <![CDATA[T5 / ℃]]> 514 511 509 446 548 515

[0055] As can be seen from Table 1, the polyimide films in Examples 1-3 have good dielectric properties. Comparative Example 1 shows that the addition of hollow nano-alumina spheres helps reduce the dielectric loss of the films. Comparative Example 2 shows that modification with isocyanate-terminated polybutadiene increases the elongation at break of the polyimide film, but weakens its thermal stability. Comparative Example 1 shows that the addition of hollow nano-alumina spheres helps balance the thermal stability of the film. Comparative Example 3 shows that the ester-linked dianhydride monomer helps increase the tensile strength of the polyimide film, thereby balancing the mechanical properties of the film.

[0056] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0057] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A process for producing a polyimide film for capacitors, characterized in that: The steps include: At 20-25° C. and under nitrogen protection, add trimellitic anhydride chloride and tetrahydrofuran to a reactor, stir and mix, then add anhydrous pyridine to the reactor, stir at 150-200 r / min for 1 hour, add 11.5wt% 1,5-dihydroxynaphthalene tetrahydrofuran solution to the reactor, stir for 12-14 hours, filter, concentrate, mix the concentrated filtrate with 0.5 times the weight of acetic anhydride, reflux at 100° C. for 10-12 hours, cool naturally, filter, wash the filter cake with anhydrous toluene, and vacuum dry to obtain an ester bond dianhydride monomer; Under nitrogen protection, add 4,4'-diaminodiphenyl ether and N,N-dimethylformamide to the reactor, stir at 0-4°C and 500-600r / min until 4,4'-diaminodiphenyl ether is completely dissolved, add ester bond dianhydride monomer to the reactor twice, with an interval of 30-40min between the two additions, stir and react for 10-12h to obtain an anhydride-terminated polyamic acid solution; Add anhydride-terminated polyamic acid solution, isocyanate-terminated polybutadiene and nano-alumina hollow spheres into a reactor, stir at 20-25°C for 3-3.5h, add 4,4'-diaminodiphenyl ether into the reactor and continue stirring for 3-3.5h, add N,N-dimethylformamide to adjust the solid content to 20%, obtain copolymer slurry, perform vacuum degassing, cast film on a steel belt at 200°C, the casting speed is 5-6m / min, remove the solvent in vacuum at 80°C to obtain a cast film, longitudinally stretch the cast film at a stretch ratio of 1:1.05 for 10-15min at 180-200°C, then transversely stretch the cast film at a stretch ratio of 1:1.15 for 15-20min, keep warm at 250°C for 30min, keep warm at 280°C for 30min, cool naturally to obtain a polyimide film for capacitors, roll it up, trim it, and complete the production process of polyimide film for capacitors.

2. The process for producing a polyimide film for capacitors according to claim 1, characterized in that: The usage ratio of the anhydride-terminated polyamic acid solution and the isocyanate-terminated polybutadiene nano-alumina hollow spheres is 30 mL: 0.25-0.35 g: 0.1-0.12 g: 0.02 g.

3. The production process of a polyimide film for capacitor according to claim 1, characterized in that: The usage ratio of the 4,4'-diaminodiphenyl ether, N,N-dimethylformamide and ester bond dianhydride monomer is 1 g:30 mL:4.43 g.

4. The process for producing a polyimide film for capacitors according to claim 1, characterized in that: The mass ratio of the trimellitic anhydride chloride, tetrahydrofuran, anhydrous pyridine and the tetrahydrofuran solution of 1,5-dihydroxynaphthalene is 10:84.5:3.8g:

33.

5. The process for producing a polyimide film for capacitors according to claim 1, characterized in that: The isocyanate-terminated polybutadiene is prepared by the following steps: Add diphenylmethane diisocyanate and N,N-dimethylformamide into a reaction kettle, stir at 150-300 r / min for 15-20 min, then add hydroxyl-terminated polybutadiene, stir and react at 60-70° C. for 6-7 h to obtain isocyanate-terminated polybutadiene.

6. The process for producing a polyimide film for capacitors according to claim 5, characterized in that: The mass ratio of the diphenylmethane diisocyanate, N,N-dimethylformamide and terminal hydroxyl polybutadiene is 27-27.5:100-120:

100.

7. The process for producing a polyimide film for capacitors according to claim 1, characterized in that: The nano-alumina hollow spheres are prepared by the following steps: Ammonia water with a concentration of 2 mol / L, ethanol aqueous solution with a concentration of 33 wt% and hexadecyltrimethylammonium bromide are added to a reaction kettle and stirred and mixed, and then a 24 wt% aluminum chloride aqueous solution is added to the reaction kettle, and the mixture is stirred at 800-1000 r / min for 60-80 min, centrifuged, filtered, and the filter cake is washed with deionized water for 2-3 times, and heat-treated at 500° C. for 5-6 h to obtain nano-alumina hollow spheres; The dosage ratio of the ammonia water, the ethanol aqueous solution, the hexadecyltrimethylammonium bromide and the aluminum chloride aqueous solution is 7-8 mL:120 mL:0.5-0.8 g:120 mL.

8. A polyimide film for capacitors, characterized in that: It is prepared by the production process described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Transparent compositions, methods for the preparation thereof, and articles derived therefrom

    CN101160340A

  • Low-dielectric heat-conducting polyimide film and preparation method thereof

    CN114874621A